Improving Students’ Reading Comprehension Through Cooperative Integrated Reading And Composition Technique - Agus Rofi'i (Universitas Majalengka, 2017)
The research aims to investigate students’ reading comprehension at the eleventh grade of Senior High School before and after using the Cooperative Integrated Reading and Composition (CIRC) technique, and also to investigate the effectiveness of CIRC technique to improve students’ reading comprehension as well. CIRC technique was chosen as the x variable in the research. The research applied pre-experimental, one group pre-test – post-test design. The population of the research was eleventh grade that consisted of five classes and class XI IPS 3 was chosen as the sample. There were 26 students in this class. The instruments used to collect the data were tests which consist of pre-test and post-test. Pre-test was conducted to investigate students’ reading comprehension before treatments. The result indicated students’ reading comprehension was fair. Meanwhile, post-test was conducted to examine students’ reading comprehension after treatments. Furthermore, it can be concluded that there is significant effect of using CIRC technique. In line with that, it can be concluded that Cooperative Integrated Reading and Composition (CIRC) technique is effective to improve students’ reading comprehension.